2016
DOI: 10.3390/d8040020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Genetic Diversity of the Macaw Palm Ex Situ Germplasm Collection Revealed by Microsatellite Markers

Abstract: Macaw palm (Acrocomia aculeata) is native to tropical forests in South America and highly abundant in Brazil. It is cited as a highly productive oleaginous palm tree presenting high potential for biodiesel production. The aim of this work was to characterize and study the genetic diversity of A. aculeata ex situ collections from different geographical states in Brazil using microsatellite (Simple Sequence Repeats, SSR) markers. A total of 192 accessions from 10 provenances were analyzed with 10 SSR, and variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…These results are congruent with those reported in other plant species (Hu et al, 2011;Song et al, 2012;Meyer et al, 2017) and can be attributed to the location of EST-SSRs in transcribed regions of the genome and therefore be less subject to variation (Ellis and Burke 2007;Varshney et al 2005). Considering gSSR and EST-SSR together, the average number of alleles detected in this study, the polymorphism index and diversity estimates (H E and H O ) (Table 2) were higher than those found by Lanes et al (2016) and Mengistu et al (2016) and lower than those reported by Lanes et al (2015) and Araujo et al (2017) in studies using only gSSR developed forA. aculeata .…”
Section: Genetic Variability In Genomic Gssrs and Est-ssrssupporting
confidence: 92%
See 2 more Smart Citations
“…These results are congruent with those reported in other plant species (Hu et al, 2011;Song et al, 2012;Meyer et al, 2017) and can be attributed to the location of EST-SSRs in transcribed regions of the genome and therefore be less subject to variation (Ellis and Burke 2007;Varshney et al 2005). Considering gSSR and EST-SSR together, the average number of alleles detected in this study, the polymorphism index and diversity estimates (H E and H O ) (Table 2) were higher than those found by Lanes et al (2016) and Mengistu et al (2016) and lower than those reported by Lanes et al (2015) and Araujo et al (2017) in studies using only gSSR developed forA. aculeata .…”
Section: Genetic Variability In Genomic Gssrs and Est-ssrssupporting
confidence: 92%
“…In the present study, microsatellite markers of expressed regions (EST-SSR) and genomic regions (gSSR) were adopted to elucidate the taxonomic relationship between the most economically important Acrocomia species (A. aculeata and A. totai ) and to identify possible interspecific hybrids. In the genus Acrocomia, several genetic studies performed with microsatellite markers were conducted with at most 8 gSSR loci developed for A. aculeata by Nucci et al (2008), as in Lanes et al (2015), Lanes et al (2016), Mengistu et al (2016), Neiva et al (2016), Araújo et al (2017), Coelho et al, (2018) and Lima et al (2020). Thus, this work represents the first study using both EST-SSR and gSSR markers in Acrocomia.…”
Section: Genetic Variability In Genomic Gssrs and Est-ssrsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, in the macaúba palm, a small number of molecular markers have been available and validated [ 32 ], and they have been used in recent studies [ 13 , 33 – 36 ]. Recently, 221 SSRs were identified in the chloroplast in a high frequency of occurrence (total mean of 1/1.75 Kb) located in intergenic spacers, coding regions, introns and tRNA genes; however, they have not been validated for the macaúba palm [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The species is diploid (2n = 30) and flowers in August to November, emitting yellow flowers in inflorescences with pronounced protogyny (Scariot et al, 1991;Montoya et al, 2015). Despite favoring cross-fertilization, the macaw palm is considered to have a mixed mating system (Nucci et al, 2008;Mengistu et al, 2016). The species has areas of open vegetation with high solar incidence as its most common habitat, and it is recognized as a soil fertility indicator.…”
Section: Introductionmentioning
confidence: 99%